Transactions Security Tools in Account Receivables Management - Anna Wodyńska (Contemporary Economics)
Large competition among goods and services suppliers caused that granting clients deferred term of payment became a standard, so in other word granting clients commercial credit is a standard. Companies try to limit credit risk by securing their trade transactions in accordance with their credit policy that determines in some way the choice of trade transaction security tools.This article presents a full range of trade transaction security tools according to the general division into personal and property securities. The author pays attention to the fact that while conducting a proper credit policy in relation to clients, a company has chances to monitor efficiently the receivables and insist on their payment as well as use, as needed, the earlier prepared trade transaction security tools.The author convinces that regardless of the choice of trade transaction security tools, or reasons leading the receivables managing person, the basic criterion of security evaluation shall be its real, checked and verified value. The pledge on an object that does not exist is not worth much. The same applies to security granted by an insolvent person.